Constructional Aspects for Safe Operation of 120 × 570 mm Ammunition - Wojciech FURMANEK (Konstrukcyjne aspekty bezpiecznej eksploatacji amunicji 120 × 570 mm, 2021)
This paper provides a characteristic of the design of 120 × 570 mm tank ammunition with particular reference to the cartridges in service in the Polish Army. The presentation of the design and technological details was primarily focused on emphasising their influence on the phenomena occurring or likely to occur during the process of ammunition operation, and to a much lesser extent related with the reference of the characteristics of the performance of the ammunition. Due to the sheer bulk of this subject matter, this paper narrowed the issues of ammunition primarily to the aspects of entry into service, transport, storage, and operation of the specified ammunition cartridges. During these operational stages, there was major focus on the issues of ammunition safety and reliable performance. Note that these aspects are not exhaustive for the topic; this paper also serves as an introduction to a future paper which will deal with safety issues during combat operation using the 120 × 570 mm tank ammunition cartridges.
Keywords: Eksploatacja amunicji